2018
DOI: 10.1152/jn.00854.2017
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlate of auditory spatial attention allocation in the superior colliculus

Abstract: This study is the physiological complement to previous behavioral work that demonstrated that rhesus monkeys are able to allocate attention about the surrounding space based on brief, broadband auditory cues. Single-unit recordings were taken from the intermediate layers of the superior colliculus (iSC) while the subjects oriented to visual and auditory targets in the context of a cuing task with their heads unrestrained. The results show a correlation between behavioral manifestations of attention allocation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Cohen et al, 2004; Huk and Shadlen, 2005). Alternatively, the superior colliculus (SC) could serve this role, as multiple studies of spatial processing have found (Jay and Sparks, 1987; Rajala et al, 2017; Wallace et al, 1996), and there is causal evidence for its role in evidence accumulation in the visual domain (Jun et al, 2021). In the absence of neural data from one of these regions in this study, a DDM was used to characterize the integration process at the computational level, providing constraints on future neurophysiological studies in regions like PPC or SC.…”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al, 2004; Huk and Shadlen, 2005). Alternatively, the superior colliculus (SC) could serve this role, as multiple studies of spatial processing have found (Jay and Sparks, 1987; Rajala et al, 2017; Wallace et al, 1996), and there is causal evidence for its role in evidence accumulation in the visual domain (Jun et al, 2021). In the absence of neural data from one of these regions in this study, a DDM was used to characterize the integration process at the computational level, providing constraints on future neurophysiological studies in regions like PPC or SC.…”
Section: Discussionmentioning
confidence: 99%
“…The push–pull fashion of interaction between voluntary attention and reflexive attention in the struggle to control the focus of attention resources has been demonstrated in higher vertebrate taxa [ 2 , 8 , 9 , 10 , 11 ]. Similarly, we found that the auditory perception of the music frogs might invoke both voluntary attention and reflexive attention.…”
Section: Discussionmentioning
confidence: 99%
“…Attention engages in different modalities including visual and auditory, and in various stages of brain functions from processing and perception of information to finally behavioral response [ 7 ]. Previous studies have found that voluntary attention and reflexive attention struggle to control the focus of attention with interaction in a push–pull fashion [ 2 ] in higher vertebrates including birds [ 8 ], mammals [ 9 ], non-human primates [ 10 ] and humans [ 11 ]. For example, behavioral evidence has shown that a sudden alarm call will cause Japanese great tits ( Parus minor ) to stop searching for food and quickly glance at their surroundings [ 12 ].…”
Section: Introductionmentioning
confidence: 99%